A global view of stratospheric gravity wave hotspots located with Atmospheric Infrared Sounder observations. Issue 2 (25th January 2013) - Hoffmann, L.; Xue, X.; Alexander, M. J.
Abstract : [1] The main aim of this study is to find and classify hotspots of stratospheric gravity waves on a global scale. The analysis is based on a 9 year record (2003 to 2011) of radiance measurements by the Atmospheric Infrared Sounder (AIRS) aboard NASA's Aqua satellite. We detect gravity waves based on 4.3 µm brightness temperature variances. Our method focuses on peak events, i.e., strong gravity wave events for which the local variance considerably exceeds background levels. We estimate the occurrence frequencies of these peak events for different seasons and time of day and use the results to find local maxima or "hotspots." In addition, we use AIRS radiances at 8.1 µm to simultaneously detect convective events, including deep convection in the tropics and mesoscale convective systems at middle latitudes. We classify the gravity wave sources based on seasonal occurrence frequencies for convection, but also by means of time series analyses and topographic data. Our study reproduces well‐known hotspots of gravity waves, e.g., the Andes and the Antarctic Peninsula. However, the high horizontal resolution of the AIRS observations also allows us to locate numerous mesoscale hotspots, which are partly unknown or poorly studied so far. Most of these mesoscale hotspots are found near orographic features like mountain ranges, coasts, lakes, deserts, or isolated islands. This study will help to select promising regions and seasons for future case studies of gravity waves. Key Points: AIRS observations provide a first global view of gravity wave peak events Hotspots are located and classified with convective or orographic sources Many hotspots are previously unidentified and will motivate new case studies